Predpisovanje antibiotikov v slovenskih zdravstvenih regijah in vzroki razlik v predpisovanju - Vrečar, Vida (Medicinski razgledi, 2009)
The aim of our retrospective study was to determine antibiotic usage in Slovenian health regions during the period of 2000-2006 and to find demographical, economical, social and other factors that would explain the differences in usage. In our retrospective study we analysed antibacterial agent usage for systemic treatment in all of the Slovenian health regions in the whole population as well as separately in both child and adult populations. During the period between 2000-2006 the average use of antibiotics was the highest in the regions of Ravne and Maribor and the lowestin the regions of Nova Gorica and Koper. In the whole population study penicillins were prescribed the most, followed by macrolides and lincozamides.In children the third most prescribed were cephalosporins followed by co-trimoxazole. In the adult population the third most prescribed was co-trimoxazole followed by quinolones. There were no correlating factors found in the whole population study. In children the number of respiratory tract infections was the only correlating factor found with regard to consumption in 2001. In those over fifteen years of age antibiotic usage was highly correlated to the duration of work absence. In those over 65 years there was highIy negative correlation with regard to work absence during the years 2002-2005. A high correlations was also found in those aged 20-44 in theyear 2002. The results represent a base for further measures in the field of appropriate antibiotic use.
Keywords: Antibiotics; Recepti za zdravila; Prescriptions, Drug; Zdravilo, uporaba; Socioekonomski faktorji; Drug Utilization; Socioeconomic Factors; Antibiotiki; antibiotic; Demografija; Demography; Ambulatory Care; Starostni faktorji; Age Factors; Ambulantna oskrba; predpisovanje zdravil; Slovenia; Slovenija